2021
DOI: 10.1126/sciadv.abf2403
|View full text |Cite
|
Sign up to set email alerts
|

The mycoplasma surface proteins MIB and MIP promote the dissociation of the antibody-antigen interaction

Abstract: Mycoplasma immunoglobulin binding (MIB) and mycoplasma immunoglobulin protease (MIP) are surface proteins found in the majority of mycoplasma species, acting sequentially to capture antibodies and cleave off their VH domains. Cryo–electron microscopy structures show how MIB and MIP bind to a Fab fragment in a “hug of death” mechanism. As a result, the orientation of the VL and VH domains is twisted out of alignment, disrupting the antigen binding site. We also show that MIB-MIP has the ability to promote the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 64 publications
2
37
0
Order By: Relevance
“…This case may be reminiscent of that for dynein, a motor in eukaryotes, which evolved from a widely conserved AAA (ATPases associated with diverse cellular activities)+ protein, in which multiple subunits of ATPases perform functional rotation ( 41 , 42 ). Sequence analyses have shown that mycoplasma type 3 ATPase is also related to F 1 -ATPase, and its role has been suggested to promote substrate turnover in the MIB-MIP system ( 33 ). If type 3 ATPase provides the force to change the conformation of a hydrolytic enzyme, its role in force generation is common with that of type 2, the gliding motor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This case may be reminiscent of that for dynein, a motor in eukaryotes, which evolved from a widely conserved AAA (ATPases associated with diverse cellular activities)+ protein, in which multiple subunits of ATPases perform functional rotation ( 41 , 42 ). Sequence analyses have shown that mycoplasma type 3 ATPase is also related to F 1 -ATPase, and its role has been suggested to promote substrate turnover in the MIB-MIP system ( 33 ). If type 3 ATPase provides the force to change the conformation of a hydrolytic enzyme, its role in force generation is common with that of type 2, the gliding motor.…”
Section: Discussionmentioning
confidence: 99%
“…Type 1, found in all mycoplasmas, is a typical operon encoding F 1 F o -ATPase and is likely to function as a proton pump to maintain membrane potential. Type 3 is found in mycoplasmas that have an MIB-MIP system to cleave host immunoglobulins ( 33 ). Type 2 is only found in four Mycoplasma species, including M. mobile .…”
Section: Introductionmentioning
confidence: 99%
“…Surface localized proteins are more potent for generating an immune response compared to other localized proteins. These proteins contain antigenic determinants and are in frequent contact with the host [84]. Moreover, they function as virulent proteins by activating immune signaling pathways [37].…”
Section: Discussionmentioning
confidence: 99%
“…E5E95_00610 gene was annotated as adhesin protein by the NCBI Search database; it experienced two non-synonymous gene mutations (C-G and C-T) according to the results of SNP analysis (Supplementary File 2), which suggested that this gene may be a new potential virulence factor, although its biological significance needs further verification. More importantly, mycoplasmas can evade the killing of the host's humoral immunity by the MIB-MIP system that captures and cleaves immunoglobulin G (61)(62)(63). E5E95_03535 was an important virulence gene encoding putative immunoglobulin-blocking protein, which could bind to the immunoglobulin in the serum to cleave the immunoglobulin, playing a crucial role in evading the neutralization of serum antibodies.…”
Section: Discussionmentioning
confidence: 99%